STRATEGIES FOR STRENGTHENING THE CULTURE OF INCLUSION IN THE REALM OF EDUCATION IN INDONESIA - Khoirin Nisa’, Syasya; Muntamah, Bening Siti; Nurdibyanandaru, Duta (JPI (Jurnal Pendidikan Inklusi), 2024)
Inclusive education is education that includes curriculum and management for all children, including those with special needs. It is important to understand the basic concepts of organizing inclusive education, one of which is using the index for inclusion. The purpose of this study is to comprehensively examine the appropriate strategies for strengthening the culture of inclusion in Indonesian inclusive schools. The method used in this research is a literature review, relying on five databases: Google Scholar, ResearchGate, Web of Science, Ebsco, and Scopus. The keywords used in the review were "Inclusive Education in Indonesia" and "Culture of Inclusion". In the end, five articles were reviewed. The result of the review is that there are important points related to strategies that can be recommended for schools in strengthening the culture of inclusion, including: 1) implementation of Positive Behaviour Support (PBS); 2) strengthening provision through socialization and training; 3) maximizing collaboration; 4) supervision and evaluation; and 5) leadership.